Perjalananku: Penggunaan Medium Elektronik (Cahaya) Dalam Karya Seni Arca - Syed Abu Bakar, Syed Alwi; Omar, Aznan; Desa, Noor Enfendi; Said Ahmad@Syed Ahmad, Siti Humaini; Razali, Rosmidahanim; Syed Omar, Sharifah Nursahilah (Idealogy Journal, 2021)
This research represents time using electronic medium through sculpture. An electronic media (light) is one of new medium in Malaysian visual arts. The use of electronic (light) as a medium, does bloom up medias in Malaysian visual arts. The exploration of this new medium, was inspired by Dan Flavin. The research includes element of light and social sharing. This research method practiced the studio base based on Wallas’ theory. This research project would benefit the societies, at the same time it would contribute to a process of creating an art works. The combination between electronic (light) and conventional medium will diverse the use of medium in producing art works. Keywords Time, Electronic (Light), Sculpture and Conventional